PARTISIPASI MEDIA SOSIAL UNTUK MEMPENGARUHI KEBIJAKAN PUBLIK PEMERINTAH KOTA PADANG - Muhammad Fadlan; Afriva Khaidir; Nora Eka Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to find out how social media participation affects the policies of the Padang City government. The method in this research is a type of qualitative research with descriptive methods. The selection of informants in this study used a purposive sampling technique. The data used in this study are primary data and secondary data. Data collection techniques in this study used observation, interviews and documentation studies. Data analysis techniques in this study used data collection techniques, data reduction, data classification, data presentation, and drawing conclusions. The results of this study the authors found that social media has an influence in government policy, want it in the making, implementing and evaluating the policies of the city of Padang.